Enhanced Resonance Magnetoelectric Coupling in (1‐1) Connectivity Composites. Issue 19 (3rd March 2017) - Chu, Zhaoqiang; Shi, Huaduo; Shi, Weiliang; Liu, Guoxi; Wu, Jingen; Yang, Jikun; Dong, Shuxiang
Abstract : Bulk‐magnetoelectric (ME) composites consisting of various piezoelectric and piezomagnetic materials with (3‐0), (3‐1), (2‐2), and (2‐1) connectivity are proposed in a bid to realize strong ME coupling for next‐generation electronic‐device applications. Here, 1D (1‐1) connectivity ME composites consisting of a [011]‐oriented Pb(Mg, Nb)O3 ‐PbTiO3 (PMN‐PT) single‐crystal fiber laminated with laser‐treated amorphous FeBSi alloy (Metglas) and operating in L‐T mode (longitudinally magnetized and transversely poled) are reported, which exhibit an enhanced resonant ME coupling coefficient of ≈7000 V cm −1  Oe −1, which is nearly seven times higher than the best result published previously, and also a superhigh magnetic sensitivity of 1.35 × 10 −13 T (directly detected) at resonance at room temperature, representing a significant advance in bulk magnetoelectric materials. The theoretical analyses based on magnetic‐circuit and equivalent‐circuit methods show that the enhancement in ME coupling can be attributed to the reduction in resonance loss of laser‐treated Metglas alloy due to nanocrystallization and the strong magnetic‐flux‐concentration effect in (1‐1) configuration composites. Abstract : A seven‐times‐higher magnetoelectric coupling (≈7000 V cm −1 Oe −1 ) than the best result published previously and also a superhigh magnetic sensitivity (1.35 × 10 −13 T) at resonance at room temperature are found from 1D (1‐1) connectivity magnetoelectric composites consisting of a [011]‐oriented Pb(Mg, Nb)O3 ‐PbTiO3 single‐crystal fiber laminated with laser‐treated amorphous FeBSi alloy (Metglas).